DOES PREOPERATIVE SURGICAL SITE HAIR REMOVAL FOR ELECTIVE ABDOMINAL SURGERY HAVE AN IMPACT ON SURGICAL SITE INFECTION? AN OBSERVATIONAL STUDY. - Hota, Smruti Ranjan; Behera, Chinmaya Ranjan; Kanungo, Abinash; Mishra, Subrajit (Student’s Journal of Health Research Africa, 2024)
Background The surgical site infection and the role of hair on the surgical site play an important role in avoiding the stated complication. This study is conducted to determine the effect of shaving on the occurrence of surgical site infection Method This was a prospective observational study conducted for a year. The participants who underwent abdominal surgery participated in the surgery. One of the two groups before the surgery had shaved, and the other did not shave. The occurrence of surgical site infection, the grading of the wound, and the grading of the pain were compared statistically among both groups. Results The study included 100 participants with a mean age of 43.5 years and a mean BMI of 22.88 kg/m². SSIs were reported in 11% of cases, with no statistically significant difference between the shaved and unshaved groups. Wound grading and pain assessment also showed no significant differences. Conclusion This study concluded that shaving did not have any effect on the occurrence of surgical site infection after the surgery. Recommendation Shaving should be avoided before performing the surgery; this decreases the chances of post-operative complications such as surgical site infection